2023
DOI: 10.3390/jcm12020695
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Models for Tinnitus Presence and the Impact of Tinnitus on Daily Life: A Systematic Review

Abstract: The presence of tinnitus does not necessarily imply associated suffering. Prediction models on the impact of tinnitus on daily life could aid medical professionals to direct specific medical resources to those (groups of) tinnitus patients with specific levels of impact. Models of tinnitus presence could possibly identify risk factors for tinnitus. We systematically searched the PubMed and EMBASE databases for articles published up to January 2021. We included all studies that reported on multivariable predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In a recent systematic review of prediction models, we noticed that demographic factors were mostly used as predictors in the final models on tinnitus experience. Whereas comorbidities were mostly used as predictors in models on tinnitus impact ( 11 ). In the current model on tinnitus experience, we found both demographic factors and comorbidities to be predictors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent systematic review of prediction models, we noticed that demographic factors were mostly used as predictors in the final models on tinnitus experience. Whereas comorbidities were mostly used as predictors in models on tinnitus impact ( 11 ). In the current model on tinnitus experience, we found both demographic factors and comorbidities to be predictors.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review of our research group, we identified four prediction models for assessing tinnitus presence. While the sample sizes of these studies were sufficient ( n = 4,950 to 168.348 per study), the statistical analyzes were often a source of bias ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Observed discrepancies in tinnitus experiences may be due variations in socio-demographic, psychological, hearing, or physical health. [9][10][11] Moreover, emotional and sleep disorders, often seen as consequences of tinnitus, may also be risk factors for its apparition or severity. In this case, psychosocial factors may instead contribute to shape how tinnitus is experienced by the patient.…”
Section: Introductionmentioning
confidence: 99%